Optimizing the User Experience of the Philippine eTravel System - Carreon, Paula Joan; Lavides, Maria Margarita R; Abad, Maria Angelica D; Cuenco, Arianne Kaye; Ladea, Laarni; Ricafranca, Marinella (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This study aims to explore the Philippine eTravel System from the users’ perspective. The PH eTravel System is an electronic platform that is supposed to help international passengers expedite their travel processes. The authors employed Design Thinking (DT) - an approach that is iterative and centered on humans in solving problems by understanding their needs, creating ideas innovatively, and testing them to arrive at meaningful and effective results. This work was carried through following the various stages of the DT process namely, empathize, define, ideate, prototype, and test. Results of data analysis revealed that the users encounter difficulties such as complicated registration procedure, malfunctions of the system, and accessibility issues specifically with individuals who are not so well versed in technology. At the end of this paper, the authors suggest innovations towards making the travel system more inclusive and user friendly. Recommendations focused on technical and administrative aspects particularly the improvement of the interface, multilingual options, availability of steady connection within airports, and different paper-based forms for special cases.